THE IMPLEMENTATION OF RECITATION METHOD LEARNING BASED ON E-MODULE TO INCREASE DISCIPLINE AND LEARNING ACHIEVEMENT OF STUDENTS (THE STUDY OF ECONOMIC SUBJECT OF SOCIAL SCIENCE TENTH GRADE STUDENTS IN SENIOR HIGH SCHOOL 1 TEBING TINGGI) - Sukma Susilawati; Turdjai Turdjai (DIADIK, 2018)
This study aims to: describe the implementation of recitation method learning based on e-module to increase discipline and learning achievement of students. This study used a class action research method, which was followed by experiments. The subjects of social science tenth grade  students in senior high school  1 tebing tinggi. Data collection techniques used are observation sheets and test. The data obtained is then processed by calculating the average value for learning and disciplinary attitudes, and for learning achievement the data obtained is processed by looking for the average value and t test formula. The results of the study conclude The Implementation Of Recitation Method Learning Based On E-Module To Increase Discipline And Learning Achievement Of Students